The National Museum of Brazil and the education sector: historical aspects of its educational function - Souza, Fernanda de Lima; Gomes, Maria Margarida (Revista CPC, 2022)
This paper discusses the social and historical constitution of the National Museum of Brazil’s Education Sector (SAE) and its educational function. Based on contributions from the curriculum field related to school subjects and on literature about museum education, its defends the importance of teaching collections produced by this sector and examines the relations developed with school institutions. Hence, the text looks at two remarkable moments in the history of this sector: its creation in the 1920s-1930s and the socialization its zoological teaching collection today. To do so, the analysis articulates literature on this sector, SAE activity reports and interviews with science and biology teachers, reflecting on social-historical aspects decisive for its creation. Moreover, it explores how the relationship between the museum and schools has been built throughout its history by producing and making available the SAE science teaching collections.